Brain Targeting Delivery Facilitated by Ligand-Functionalized Layered Double Hydroxide Nanoparticles - Chen, Weiyu; Zuo, Huali; Zhang, Enqi; Li, Li; Henrich-Noack, Petra; Cooper, Helen; Qian, Yujin; Xu, Zhi Ping (ACS applied materials & interfaces, 2018)
A delivery platform with highly selective permeability through the blood-brain barrier (BBB) is essential for brain disease treatment. In this research, we designed and prepared a novel target nanoplatform, that is, layered double hydroxide (LDH) nanoparticle conjugated with targeting peptide-ligand Angiopep-2 (Ang2) or rabies virus glycoprotein (RVG) via intermatrix bovine serum albumin for brain targeting. In vitro studies show that functionalization with the target ligand significantly increases the delivery efficiency of LDH nanoparticles to the brain endothelial (bEnd.3) cells and the transcytosis through the simulated BBB model, that is, bEnd.3 cell-constructed multilayer membrane. In vivo confocal neuroimaging of the rat's blood-retina area dynamically demonstrates that LDH nanoparticles modified with peptide ligands have shown a prolonged retention period within the retina vessel in comparison with the pristine LDH group. Moreover, Ang2-modified LDH nanoparticles are found to more specifically accumulate in the mouse brain than the control and RVG-modified LDH nanoparticles after 2 and 48 h intravenous injection. All these findings strongly suggest that Ang2-modified LDHs can serve as an effective targeting nanoplatform for brain disease treatment.